Etiological Evaluation of Pancytopenia in a Tertiary Care Hospital: A Prospective Study - Anuja Dasgupta; Shetty K. Padma; K. Sajitha; Jayaprakash Shetty (Issues and Development in Health Research Vol. 4, 2021)
Background: Pancytopenia is not a disease by itself; but a common hematological problem which is characterized by simultaneous presence of anemia, leucopenia and thrombocytopenia. The disease pattern associated with pancytopenia varies with geographic location, age group, nutritional status, drug intake and prevalence of infective disorder. This prospective study was to investigate and identify different causes of pancytopenia, to ascertain percentage of occurrence of pancytopenia, and to determine its incidence in relation to sex and age, as well as to compare the findings with those of other similar studies. Methods: 80 patients diagnosed with pancytopenia were clinically evaluated, with complete blood count, peripheral smears, and bone marrow aspiration-biopsy whenever possible in Justice K. S. Hegde Hospital attached to Nitte University, Deralakatte, Mangalore, from June 2012 to June 2014. Results: Among the 80 cases analyzed, most of the cases were seen in the age group of 41-50 years, with male predominance. Hypersplenism (28.75%), malaria (16.25%) and megaloblastic anemia (13.75%) were the three commonest causes in our hospital. In 13 cases of malaria, Plasmodium vivax (8 cases) was most commonly noted. Conclusion: The present study concludes that varied causes of pancytopenia can be attributed to the geographic area, nutritional and drug intakes, personal habits, infective causes, stringency of diagnostic criteria, and differences in methodology used. Hence, a detailed clinical history and meticulous examination along with hematological investigations provide invaluable information in the complete workup of patients with pancytopenia for understanding the disease processes, planning further investigations and management, and ascertain the cause.